"What is disability? It depends whose shoes you are wearing": Parent understandings of the concept of disability - Cologon, Kathy (Disability Studies Quarterly, 2016)
This study investigates parent perspectives on the meaning of 'disability'. One hundred and twenty-one parents in Australia, each of whom have one or more children labelled with impairments, participated in this study. Parent definitions of disability are considered in light of the contrasting dominant deficit discourse involved in the medical model pathologizing of children labelled with impairments, and the social model positioning of disability as oppression of a minority group. Thematic analysis is used to examine parent views and to consider the relevance of social and medical models of disability to families. This study, that forms part of a larger study on family experiences of inclusion and exclusion, contributes to developing a deeper understanding of family experiences and the ways in which parents define disability. Overall, Thomas' social relational model of disability was found to be particularly salient to understanding the experiences of the families participating in this study.